The Influence of Sponsorship on Marketing Development Fun Run in Central Java - Agus Pujianto; Edi Purwanto; Amin Pujiati; Sucihatiningsih Dian Wisika Prajanti (Journal of Physical Education Health and Sport, 2024)
This study aims to analyze the influence of sponsorship on the marketing and development of fun run sports in Central Java. Fun run as a type of recreational sport is increasingly in demand by various groups of people. The involvement of sponsors in this activity plays an important role in increasing the attraction, participation, and success of the event. Sponsorship makes a significant contribution through financial support, provision of facilities, and promotion. This study uses a quantitative approach with a survey of participants and organizers and sponsors involved in fun run events specifically in the Central Java region. The results of the analysis show that sponsorship has a positive impact on increasing brand awareness, increasing the number of participants participating in the Fun Run, and can ensure the sustainability of the event effectively. Thus, the sustainability of the relationship between organizers and sponsors is a key factor in supporting the marketing and development of fun runs in Central Java.